THE INFLUENCE OF THE PRINCIPAL'S LEADERSHIP AND MANAGERIAL AGAINST PERFORMANCE COMPETENCY OF STATE MIDDLE SCHOOL TEACHERS IN BANDUNG REGENCY - Kirana Lesmi; Wahyu Triono; Iim Khotimah; Sutarman Sutarman (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to analyze the influence of leadership and managerial principals on teacher performance competencies. The research method uses quantitative analysis with the hypothesis in the research, namely: First, there is an influence from the principal's leadership on teacher performance competencies. Second, there is the head's managerial influence on teacher performance competencies. Third, there is also the simultaneous influence of leadership and managerial principals on teacher performance competencies. With a population of a number of teachers and principals and their representatives at Public Junior High Schools in Bandung district in 2021. With a sample of 250 teachers, principals and their deputies, the sample was taken proportionally at random. Data collection techniques with a questionnaire using an instrument with a total of 80 statements from respondents. Quantitative analysis with statistical calculations, using simple regression correlation, and multiple regression. Conclusion (1). There is a significant influence on the principal's leadership on teacher performance competence, (2). On the significant influence of managerial principals on teacher performance competencies, (3). There is also a significant influence of the principal's leadership and managerial simultaneously on teacher performance competence, with a multiple correlation coefficient = 0.715 with a coefficient of determination = 51.0%.